2019
DOI: 10.3389/fmicb.2019.01148
|View full text |Cite
|
Sign up to set email alerts
|

Switching the Post-translational Modification of Translation Elongation Factor EF-P

Abstract: Tripeptides with two consecutive prolines are the shortest and most frequent sequences causing ribosome stalling. The bacterial translation elongation factor P (EF-P) relieves this arrest, allowing protein biosynthesis to continue. A seven amino acids long loop between beta-strands β3/β4 is crucial for EF-P function and modified at its tip by lysylation of lysine or rhamnosylation of arginine. Phylogenetic analyses unveiled an invariant proline in the -2 position of the modification site in EF-Ps that utilize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 95 publications
(157 reference statements)
1
24
0
Order By: Relevance
“…Whether this mode of action also applies for FrlR we examined the dimerization tendency in vitro and in vivo . For the in vivo analysis, the bacterial-two-hybrid system described by Karimova et al was employed (Karimova et al , 1998) with the exception that all experiments were carried out with our recently published reporter strain, that has a luminescence reporter readout in addition to the original LacZ based colorimetric one (Volkwein et al , 2019). Based on the FrlR homology modeling (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this mode of action also applies for FrlR we examined the dimerization tendency in vitro and in vivo . For the in vivo analysis, the bacterial-two-hybrid system described by Karimova et al was employed (Karimova et al , 1998) with the exception that all experiments were carried out with our recently published reporter strain, that has a luminescence reporter readout in addition to the original LacZ based colorimetric one (Volkwein et al , 2019). Based on the FrlR homology modeling (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This system is based on functional reconstitution of split Bordetella pertussis adenylate cyclase CyaA, which catalyzes the formation of cyclic AMP from ATP. In E. coli KV1, the cAMP depedent lac promoter P lac precedes a translational fusion of the lux -operon and lacZ , allowing the indirect measurement of protein-protein-interactions by light emission and colorimetric detection (Volkwein et al , 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The latter enzyme is phylogenetically unrelated to EpmA and thus favored strong co‐evolution of the corresponding EF‐P at the sequence level, while the structure has remained highly conserved [17]. Although the EF‐Ps of P. putida and E. coli share only 26% sequence identity, we have recently shown that cross‐modification and even activation by EarP is possible with only few amino acid replacements in EF‐P [57]. Conversely, future studies will clarify whether EpmA can recognize the P. putida EF‐P.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this mode of action also applies for FrlR Eco , we examined the dimerization tendency in vitro and in vivo. For the in vivo analysis, the bacterial two-hybrid system (BTH) described by Karimova et al was employed (Karimova et al, 1998) with the exception that all experiments were carried out with our recently published reporter strain, that has a luminescence reporter readout in addition to the original LacZ based colorimetric one (Volkwein et al, 2019). Based on the FrlR Eco homology modeling (Figure 3), we split the protein into two parts, one comprising the N-terminal DNA-binding domain (aa 1-77), the other one encompassing the C-terminal UTRA domain (aa 78-244) and fused them to the T25 and T18 fragments of Bordetella pertussis adenylate cyclase.…”
Section: Frlr Eco Dimerizes Via Its C-terminal Utra Domainmentioning
confidence: 99%
“…In E. coli KV1, the cAMP depedent lac promoter P lac precedes a translational fusion of the lux-operon and lacZ, allowing the indirect measurement of protein-protein-interactions by light emission and colorimetric detection (Volkwein et al, 2019).…”
Section: Bacterial Two-hybrid Assaymentioning
confidence: 99%